Separation and enrichment of trace ractopamine in biological samples by uniformly-sized molecularly imprinted polymers - Ya Li; Qiang Fu; Meng Liu; Yuan-Yuan Jiao; Wei Du; Chong Yu; Jing Liu; Chun Chang; Jian Lu (Elsevier, 2012)
In order to prepare a high capacity packing material for solid-phase extraction with specific recognition ability of trace ractopamine in biological samples, uniformly-sized, molecularly imprinted polymers (MIPs) were prepared by a multi-step swelling and polymerization method using methacrylic acid as a functional monomer, ethylene glycol dimethacrylate as a cross-linker, and toluene as a porogen respectively. Scanning electron microscope and specific surface area were employed to identify the characteristics of MIPs. Ultraviolet spectroscopy, Fourier transform infrared spectroscopy, Scatchard analysis and kinetic study were performed to interpret the specific recognition ability and the binding process of MIPs. The results showed that, compared with other reports, MIPs synthetized in this study showed high adsorption capacity besides specific recognition ability. The adsorption capacity of MIPs was 0.063Â mmol/g at 1Â mmol/L ractopamine concentration with the distribution coefficient 1.70. The resulting MIPs could be used as solid-phase extraction materials for separation and enrichment of trace ractopamine in biological samples. Keywords: Ractopamine, Uniformly-sized molecularly imprinted polymers, Solid-phase extraction, Multi-step swelling and polymerization, Separation and enrichment